Posterior migration of lumbar disc herniation - imaging dilemma due to contrast contraindication: a case report - Gonçalves,Fabrício Guimarães (2012)
Disc herniation with posterior epidural migration is a rare and often symptomatic entity. Multiple are the natural barriers that prevent this pattern of migration. Enhanced magnetic resonance imaging is the diagnostic modality of choice in these cases. The diagnostic dilemma in this case was the contraindication to the use of contrast since the patient was known to have chronic renal failure.